2021
DOI: 10.4103/joco.joco_226_20
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Ocular Surface Disease in Tunisian Users of Preserved Antiglaucomatous Eye Drops

Abstract: Purpose: To study the clinical and the functional findings in glaucomatous patients under preserved eye drops having ocular surface alterations and to analyze their risk factors. Methods: A cross-sectional study of 155 glaucomatous patients was conducted. All of them answered the “Ocular Surface Disease Index” (OSDI) questionnaire and had a complete and precise evaluation of the ocular surface state including a Schirmer I test, a tear break-up time evaluation, eyelid, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Wong et al measured TMH by taking three measurements near the center of the lower meniscus with pre-calibrated digital imaging and then averaging them and found that TMH was significantly poorer in treated eyes as compared to fellow eye ( P = 0.03) but the long-term effects on tear meniscus were not assessed by them since that was a cross-sectional study. [ 20 ] A study done by Agnifili et al compared tear meniscus parameters in medically controlled glaucoma patients, patients with evaporative dry eye, and healthy controls, and found similar results as our study. [ 13 ]…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Wong et al measured TMH by taking three measurements near the center of the lower meniscus with pre-calibrated digital imaging and then averaging them and found that TMH was significantly poorer in treated eyes as compared to fellow eye ( P = 0.03) but the long-term effects on tear meniscus were not assessed by them since that was a cross-sectional study. [ 20 ] A study done by Agnifili et al compared tear meniscus parameters in medically controlled glaucoma patients, patients with evaporative dry eye, and healthy controls, and found similar results as our study. [ 13 ]…”
Section: Discussionsupporting
confidence: 90%
“…Studies done by Ramli et al and Lajmi et al found that Banzalkonium Chloride (BAK) was the major factor associated with higher OSDI scores. [ 15 18 20 ] Ramli et al found a significantly higher OSDI score in the glaucoma group as compared to controls along with rates of abnormal OSDI nearly three times more in subjects who were on BAK containing anti-glaucoma drops but they found no correlation in increased differences in OSDI results and the number of eye drops. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In neither of the four investigations was the type of preservative characterized [ 16 , 17 , 18 , 19 ]. In a study carried out in Tunisia, 80.0% of the patients received antiglaucoma drugs with BAK [ 36 ]. In this report, a wide use of BAK was found, which is the most commonly used preservative in ophthalmology [ 9 , 11 , 21 ] and is linked to cytotoxic damage to the epithelial cells of the conjunctiva and cornea, which can lead to signs and symptoms of ocular surface disease [ 9 , 11 ] and contributes to the adherence and persistence of the use of antiglaucoma agents [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“… 56 Another Tunisian study of 155 medically-managed patients with glaucoma reported that the main risk factors for DED were advanced age, duration of glaucoma treatment, use of multiple therapies, and the use of antiglaucoma medications containing BAK. 57 Although specific data are lacking for MENA, generally, DED can also be caused by estrogen-containing hormone replacement therapies, antihistamines, and psychotropic drugs, many of which reduce lacrimal secretion. 49 Caffeine may also be associated with increased risk for DED, 58 but the available data are not yet consistent enough to draw a firm conclusion.…”
Section: Introductionmentioning
confidence: 99%